How is the Turkish Housing Market Taking its New Shape? - Aydın, Yahya; Üstün, Alkan; Üstün, Alkan (My University, 2022)
While being a homeowner is a common and acceptable demand in many societies around the world, it is not possible for all members of all societies to easily access their own property. This situation is a common experience in Turkey as well; indeed, there has been a steady decline in homeownership rates in Turkey since 2013. Based on official and independent statistics, buying a house is getting harder every year in Turkey. This paper will examine the current Turkish housing market to answer the research question: What are the key factors affecting the Turkish housing market in terms of distribution of homeownership and tenantry? The research basically relies on secondary data on the Turkish housing market. According to the findings obtained in the study, both national and global factors have played role in buying tendencies in the Turkish house market. Inflation and financial issues, a decrease in purchasing power, increased building costs, migration, and purchasing behaviours of housing consumers are amongst the more prominent factors dominating the housing market in Turkey.
Keywords: İşletme; İktisat; Kentsel Çalışmalar; Turkey.; Inequality; Housing Market; Home Ownership; Urbanisation